Original articleCoexistence of meningioma and schwannoma in the same cerebellopontine angle in a patients with NF2 - Matyja, Ewa; Kunert, Przemysław; Grajkowska, Wieslawa; Marchel, Andrzej (Folia Neuropathologica, 2012)
The coexistence of schwannoma and meningioma in the same cerebellopontine angle (CPA) is uncommon. Especially, the presence of a single mixed tumour composed of demarcated or intermingled components of schwannoma and meningioma tissue is extremely rare. Such a phenomenon is mainly reported in a patient with NF2 or with history of previous irradiation. We present two cases of simultaneous occurrence of schwannoma and meningioma in the same cerebellopontine angle in young adult patients with clinical manifestation of NF2. The first patient was a 18-year-old young man who presented with bilateral CPA tumours, spinal mass lesion and multiple, small, schwannoma-like lesions of the cauda equina. Both CPA tumours was initially diagnosed as schwannomas based on preoperative MR imagings, however right CPA tumour appeared to be composed of a well-circumscribed transitional meningioma located inside schwannoma of Antoni A and B type. The second patient, a young 16-year-old boy, presented bilaterall CPA tumours as well as many meningeal tumours supratentorially and infratentorially. Two adjacent tumours in the left CPA proved to be schwannoma and meningioma. In both cases, the different neoplastic components were confirmed by histopathological and immunohistochemical studies. The possible mechanism underlying the occurrence of such coexisting tumors of different histogenesis remains unclear.